Influ??ncia do perfil psicol??gico de g??nero sobre os n??veis de estresse e de aptid??o f??sica relacionada ?? sa??de em integrantes do BOPE/PI - Dutra J??nior, En??as de Freitas (2012)
It is proven fact that the practice of physical activity is effective in combating stress, however with the Interactive Model creation, proposed to assess gender schemas of the self-concept, classifying the subject into three main groups, Heteroesquem??ticos Male, Isoesquem??ticos and Hetroesquem??ticos Female where there is an association between behavioral consistency according to the group to which belongs, it is important that the correlation between psychological profile of gender, physical fitness and stress to understand attitudes and behaviors of different subjects on different situations. Therefore this study had as objective to evaluate the influence of psychological gender profile of men integrant of a Military Police Battalion of the State of Piau?? about their levels of stress and physical fitness health-related. Method: the study is characterized as descriptive, quantitative, observational and correlational and was developed with 42 members of the Tactical Actions Group of the military police of the State of Piau??, all male. As data collection instruments were used the Male Gender Schemas' Inventory of Self-concept - IMEGA to evaluate the psychological gender profile and the Factorial Model of Stress - MFE to evaluate the stress level, healthrelated physical fitness was evaluated by applying motor tests as flexibility, strength/ localized muscular endurance (abdominal and elbow flexion), 12-minute test, in addition to these was held also the evaluation of fat % with skinfold method through the 7 site equation proposed by Jackson and Pollock. The results demonstrated that soldiers presented only two typological gender groups, Isoesquem??ticos (61%) and Heteroesquem??ticos Male (39%), about the results of motor tests for flexibility was 37.4 ?? 8.52 centimeter, abdominals was 49.75 ?? 6.68 repetitions per minute, elbows flexion was 43 ?? 11.45 repetitions, VO2max was 45.22 ?? 3.45 ml (kg/min) -1 and fat % was 11.65 ?? 4.02. As for the stress, the soldiers did not show high levels of stress. Conclusions: Although the results of the psychological profile of Gender are consistent with the characteristics of the profession of the subjects of the sample, it was found that there is no influence of the psychological profile of genre on physical fitness levels or about stress levels.